EKSPOSISI TEKS ALKITAB BAGI PENINGKATAN KETERAMPILAN BERKHOTBAH PARA PENATUA GEREJA PUNGUAN KRISTEN BATAK LUMBAN TONGATONGA - Erman Saragih; Arip Surpi Sitompul; Nurelni Limbong; Iwan Setiawan Tarigan; Bernhardt Siburian; Bresman Sihotang; Jihan Panggabean (Unika Santu Paulus Ruteng, 2023)
Preaching skills are one of the competency requirements of the elders of the Gereja Punguan Kristen Batak (GPKB). However, based on the results of observations and discussions with the pastor in charge of GPKB Lumban Tongatonga, the problems and obstacles that occur are aspects of elder competence in digging into the Bible and communicative preaching skills that are still not optimal. The image of church elders is, of course, they are seen by the congregation as people who have the competence and can support the development of church ministry through the sermons they deliver. As a GPKB partner institution, the Program Studi Teologi was moved to provide ways to explore Bible texts in improving expository preaching skills for the